2006
DOI: 10.1097/01.psy.0000195967.51768.ea
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status, Race, and Diurnal Cortisol Decline in the Coronary Artery Risk Development in Young Adults (CARDIA) Study

Abstract: Lower SES was associated in a graded fashion with flatter diurnal rhythms as a result of less of a decline during the evening. This association occurred independent of race and the data were consistent with mediation by health practices, emotional and social factors. Blacks also showed a flatter rhythm at the end of the day. This association was independent of SES and could not be explained by behavioral, social, or emotional mediators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

48
352
4
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 354 publications
(407 citation statements)
references
References 32 publications
48
352
4
3
Order By: Relevance
“…Since AA adults show worse health status at each stage of adulthood than their White counterparts (37-39) the former group may be especially vulnerable to the perils of caregiver stress. For instance, young AA adults show flatter daily cortisol slopes than their White counterparts (35). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since AA adults show worse health status at each stage of adulthood than their White counterparts (37-39) the former group may be especially vulnerable to the perils of caregiver stress. For instance, young AA adults show flatter daily cortisol slopes than their White counterparts (35). …”
Section: Discussionmentioning
confidence: 99%
“…The values for each time point were also evaluated but will not be included in the current paper for the sake of simplicity in analytical focus. More positive values which signify flatter daily cortisol slopes imply increased risk for chronic disease (35). Correlational analyses were run for cortisol response, sociodemographic, caregiving and psychosocial variables.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, lower levels of morning cortisol have been described among blacks compared with whites, while accounting for perceived stress (Bennett et al, 2004). There is also evidence that race and ethnicity influences the diurnal variations in cortisol (Cohen et al, 2006;Gallagher-Thompson et al, 2006;McCallum et al, 2006). For instance, one study reported that blacks exhibit a flatter cortisol rhythm at the end of the day relative to whites, independent of socioeconomic status (Cohen et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that race and ethnicity influences the diurnal variations in cortisol (Cohen et al, 2006;Gallagher-Thompson et al, 2006;McCallum et al, 2006). For instance, one study reported that blacks exhibit a flatter cortisol rhythm at the end of the day relative to whites, independent of socioeconomic status (Cohen et al, 2006). Similarly, another study showed that black females have flatter cortisol slopes during the day compared with their white counterparts (McCallum et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation